SYNTHESIS AND CHARACTERIZATION OF NANO CHITOSAN-AVOCADO SEED STARCH AS EDIBLE FILMS - Suhartini; Imas Solihat; Foliatini; Sri Redjeki Setyawati; Nurdiani; Lilis Sulistiawaty; Muhammad Fadhil Khoirurrizal (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
The use of plastic as food packaging tends to cause problems because it is difficult to decompose; therefore, it can pollute the environment. The development of biodegradable plastics is an alternative to this problem. Chitosan, a bioplastic, can be used as a packaging material but has poor barrier properties. A biodegradable film was made from a mixture of plasticizer, nano chitosan, and avocado seed starch. Nanochitosan synthesis was carried out using the UAE method for 2 h at an amplitude of 50% to produce 0.7 µm sized particles. Films were formed using the casting method, and characterization was performed, which included functional group, thickness, color, and antioxidant tests. The FTIR spectrum showed that the interaction between nanochitosan and avocado seed starch occurred physically, marked by a shift in the wavenumber of the amide carbonyl group from 1646.60 cm-1 1549.99 cm-1. The film thickness was 0.10–0.15 cm with a darker color as the volume of nanochitosan used increased. Antioxidant analysis revealed that the LC50 value was between 150-250 ppm. The barrier properties of the resulting film against water vapor can inhibit strawberry fruit decay for 3–4 days at room temperature.